The key to life satisfaction in emerging adults: unlocking the secrets of self-efficacy and physical activity - Luo, Lin (Frontiers in Public Health, 2024)
PurposeThis study aimed to explore the relationships among characteristics of emerging adulthood, self-efficacy, and physical activity behaviors, and how these factors collectively influence the life satisfaction of college students. By delving into the interconnections between these elements, insights for relevant interventions and policy formulation can be provided.MethodsIn this cross-sectional study conducted from November to December 2022, a total of 3,387 Chinese college students were surveyed via the Maike electronic questionnaire platform. The Inventory of the Dimensions of Emerging Adulthood (IDEA), General Self-Efficacy Scale (GSE-8), Physical Activity Rating Scale (PARS-3), and a single-item life satisfaction question were utilized for assessments. Data analysis was performed using the Bollen–Stine bootstrap method, with the aid of Amos software (version 26.0) and IBM SPSS (version 26.0).ResultsInstability, possibility, and self-exploration were significantly associated with self-efficacy, which in turn influenced life satisfaction. Factors such as possibility and instability were related to physical activity behaviors, further predicting life satisfaction. Characteristics of emerging adulthood indirectly affected life satisfaction through self-efficacy and physical activity behaviors.ConclusionCharacteristics of emerging adulthood enhance life satisfaction by bolstering self-efficacy and promoting physical activity behaviors.